The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.bioconjchem.5b00111
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Microarrays Utilizing Site-Specific Antibody–Oligonucleotide Conjugates

Abstract: Protein arrays are typically made by random absorption of proteins to the array surface, potentially limiting the amount of properly oriented and functional molecules. We report the development of a DNA encoded antibody microarray utilizing site-specific antibody–oligonucleotide conjugates that can be used for cell immobilization as well as the detection of genes and proteins. This technology allows for the facile generation of antibody microarrays while circumventing many of the drawbacks of conventionally pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(64 reference statements)
0
18
0
1
Order By: Relevance
“…To simplify the immunoassay procedure, in this study, we developed a RFIA method using synthetic covalent BaP antibody-DNA conjugates for recognition and signal amplication by using the reported detection strategy of antibody-DNA complexes. 25,27,28 As illustrated in Fig. 1, the -NH 2 -modied reporter DNA and BaP antibody were activated with sulfo-SMCC and SATA, respectively; and the two activated molecules then react to form an immune complex covalently coupled with reporter DNA and BaP antibodies for immunodetection of BaP.…”
Section: Resultsmentioning
confidence: 99%
“…To simplify the immunoassay procedure, in this study, we developed a RFIA method using synthetic covalent BaP antibody-DNA conjugates for recognition and signal amplication by using the reported detection strategy of antibody-DNA complexes. 25,27,28 As illustrated in Fig. 1, the -NH 2 -modied reporter DNA and BaP antibody were activated with sulfo-SMCC and SATA, respectively; and the two activated molecules then react to form an immune complex covalently coupled with reporter DNA and BaP antibodies for immunodetection of BaP.…”
Section: Resultsmentioning
confidence: 99%
“…The oligonucleotide labelling strategies are usually non-selective. [193,194] However, the site-specificity during immobilization can be achieved via unnatural amino acid [195,196] or oligonucleotide labelled protein G [197]. The immobilization via oligonucleotide hybridization is simple but efficient approach and suitable for surface regeneration in a timely manner.…”
Section: Antibody Immobilization Chemistriesmentioning
confidence: 99%
“…In addition, antibody with site-specifically labelled oligonucleotides can be produced using p -acetylphenylalanine incorporated antibody and aminoxy-functionalized single-stranded oligonucleotide, which resulted in a stable oxime linkage. [195,196] It has been shown that few such amino acids, such as p -benzoyl- L -phenylalanine, can work as photo-reactive crosslinker for covalently coupling antibody and its affinity partner, where the photo-reactive crosslinker could be incorporated into either antibody or its affinity partner. [169,202]…”
Section: Antibody Immobilization Chemistriesmentioning
confidence: 99%
“…The HER2‐positive cells were shown to bind specifically to the antibody–DNA microarray with a >1000‐fold difference in signal relative to the HER2‐negative cells (MDA‐MB‐231) . This type of microarray may be useful in screening for biological markers of selected tumor types that may result in the early detection and treatment of cancer.…”
Section: Miscellaneous Examplesmentioning
confidence: 99%